2014
DOI: 10.9738/intsurg-d-13-00068.1
|View full text |Cite
|
Sign up to set email alerts
|

Early Versus Delayed Laparoscopic Cholecystectomy for Acute Cholecystitis: A Prospective, Randomized Study

Abstract: We aimed to compare the clinical outcome and cost of early versus delayed laparoscopic cholecystectomy for acute cholecystitis. Sixty patients with acute cholecystitis were randomized into early (within 24 hours of admission) or delayed (after 6-8 weeks of conservative treatment) laparoscopic cholecystectomy groups. There was no significant difference between study groups in terms of operation time and rates for conversion to open cholecystectomy. On the other hand, total hospital stay was longer (5.2 6 1.40 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 17 publications
8
77
0
Order By: Relevance
“…Several authors have also described the advantages of performing surgery as early as possible from the onset of AC, which might lead to the reduction of total hospital stay, hospital charges and episodes of illness. (6,11,13,14,21) In the present study we compared the surgical outcomes between the PGD group and the EO group in order to evaluate the effect of PGD on surgery. Interestingly the data in the PGD group showed that blood loss was significantly reduced and operation time was significantly extended compared to the EO group.…”
Section: Discussion Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have also described the advantages of performing surgery as early as possible from the onset of AC, which might lead to the reduction of total hospital stay, hospital charges and episodes of illness. (6,11,13,14,21) In the present study we compared the surgical outcomes between the PGD group and the EO group in order to evaluate the effect of PGD on surgery. Interestingly the data in the PGD group showed that blood loss was significantly reduced and operation time was significantly extended compared to the EO group.…”
Section: Discussion Discussionmentioning
confidence: 99%
“…(1,2) The usefulness of early operations has been often previously reported, (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) and in principle we perform surgery as soon as possible for AC. However, there are some cases in which preoperative gallbladder drainage (PGD) should precede surgery due to the high risk to the patient, severity of AC or difficult situations of emergency operation (EO) within 72hrs from the onset such as the hospital system and a lack of surgeons.…”
Section: Introduction Introductionmentioning
confidence: 89%
“…Several other studies too have reported the similar finding ELC being better than DLC. [16][17][18][19] As is evidenced above, most of the studies depict that ELC is better DLC for outcomes such as mortality, morbidity, cost and length of stay. Some studies have even discussed the rare complications that may occur surgically or post operatively.…”
Section: Early Versus Delayed Cholecystectomymentioning
confidence: 99%
“…In Ozkardes et al [8], all patients had tenderness and pain in the upper abdominal area and 90% had Murphy sign positive. In Chau et al [18], 96.1% of patients presented with abdominal pain, 62.6% of patients had fever.…”
Section: Postoperative Hospital Staymentioning
confidence: 99%
“…Generalized peritonitis may result from GB perforation, or may be contained by the omentum leading to localized suppuration [3,7,8].…”
mentioning
confidence: 99%